2011
DOI: 10.1111/j.1600-0846.2011.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of particle systems visualization on the skin surface by scanning electron microscopy and transparency profilometry

Abstract: Profilometry enabled us to observe the systems distribution on a cutaneous texture. In addition, SEM, thanks to its high magnifications and field depth, allowed us to evaluate particles' distribution on the skin texture and the interaction between particles of different compositions and replica silicone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The use of replicas is time-consuming and, therefore, not feasible in an outpatient setting. In addition, air bubbles, gravity, and patient movement may have an effect on the quality of the replica [ 37 ]. Another measurement method is the use of skin biopsy specimens but this technique is invasive [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of replicas is time-consuming and, therefore, not feasible in an outpatient setting. In addition, air bubbles, gravity, and patient movement may have an effect on the quality of the replica [ 37 ]. Another measurement method is the use of skin biopsy specimens but this technique is invasive [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to image analysis, the study of skin roughness can be resorted to in a quantitative manner, using methods that are scientifically validated and often used in clinical studies 42 …”
Section: Resultsmentioning
confidence: 99%
“…Thanks to image analysis, the study of skin roughness can be resorted to in a quantitative manner, using methods that are scientifically validated and often used in clinical studies. 42 As explained above, thanks to Ra and Rz values measured at time 0 and after treatment, we can investigate the functionality of the cosmetic product with an anti-aging claim.…”
Section: Anti-aging Effectmentioning
confidence: 99%
“…Furthermore a constant pressure of about the gel applied on the skin must be applied in order to obtain replicas with reproducible thickness [Bogner et al 2007]. Perugini et al demonstrated how the association of skin replica and Scanning Electron Microscopy (SEM) can be used for in vivo visualization of solid lipid nanoparticles on the skin surface [Perugini et al, 2011]. The results highlighted that particle with different matrix composition had a different behaviour.…”
Section: Replicamentioning
confidence: 99%